1991
DOI: 10.2307/4002945
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Atriplex canescens for Greater Tolerance to Competition

Abstract: Success in establishing fourwing saltbush [A triplex canescens (Pursh) Nutt.] is often limited by competition from associated vegetation. Fourwing saltbush is reported to have abundant natural genetic variation, hence selection for plant vigor or competitiveness may be an effective tool for cultivar improvement. We observed distinctive within-accession variation in the apparent ability of founving saltbush seedlings to tolerate competition from sideoats gama [Bouteloua curtipendula (Michx.) Torr.] in a 1982 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Pistillate and staminate plants of 4 tetraploid (J. Barrow, USDA-Agricultural Research Service, personal communication, February 2004) western Texas ecotypes of fourwing saltbush that exhibited superior seed and pollen production in common nursery and field plantings at the Texas A&M University Agricultural Research & Extension Center near San Angelo, Texas, were propagated vegetatively in autumn 1986 from stem cuttings (Ueckert and Petersen 1991). The use of such clones should be advantageous because superior traits for seed orchard plants (seed and pollen production) show constancy from year to year (McArthur et al 1978).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pistillate and staminate plants of 4 tetraploid (J. Barrow, USDA-Agricultural Research Service, personal communication, February 2004) western Texas ecotypes of fourwing saltbush that exhibited superior seed and pollen production in common nursery and field plantings at the Texas A&M University Agricultural Research & Extension Center near San Angelo, Texas, were propagated vegetatively in autumn 1986 from stem cuttings (Ueckert and Petersen 1991). The use of such clones should be advantageous because superior traits for seed orchard plants (seed and pollen production) show constancy from year to year (McArthur et al 1978).…”
Section: Methodsmentioning
confidence: 99%
“…It would also eliminate the inconvenience of locating acceptable wildland stands and obtaining permits or permission to harvest seeds (McArthur et al 1978). Fourwing saltbush can be vegetatively propagated (cloned), and this facilitates the selection and increase of plants with desirable traits (Wiesner and Johnson 1977;McArthur et al 1978;Ueckert and Petersen 1991). McArthur et al (1978) proposed a design for fourwing saltbush seed orchards and suggested that seed orchards could be a profitable enterprise on marginal agricultural lands.…”
Section: Introductionmentioning
confidence: 99%